Effects of Interference on Wireless Mesh Networks: Pathologies and a Preliminary Solution - Li, Yi; Qiu, Lili; Zhang, Yin; Mahajan, Ratul; Zhong, Zifei; Deshpande, Gaurav; Rozner, Eric (HotNets, 2007)
We highlight two fundamental problems that degrade the throughput of wireless mesh networks today. First, severe performance degradation can occur when sources send more trafﬁc than what the network can support. The degradation can be sharp even in a simple setting of a single ﬂow that traverses a network of two links. Second, current routing protocols fail to identify high throughput routing paths even when they exist. The underlying culprit in both cases is interference that is fundamental to wireless networks. As a ﬁrst step towards a solution, we develop a novel approach to systematically account for and control interference in the network. Our approach uses (an approximation of) a formal model of interference to estimate the maximum rate at which ﬂows can safely send trafﬁc without overloading the network. Simulation and testbed experiments show that it can improve network throughput by as much as 50-100% in some conﬁgurations.